Feed Passage in Broilers - A Complex Problem - Gary D. Butcher; Amir H. Nilipour; Richard D. Miles (EDIS)
“Feed passage,” or, more accurately, the passage of undigested feed in the feces of broilers, continues to be reported in broiler integrations on a sporadic basis. The incidence and severity are much lower at present than during 1996 when global reports of feed passage occurred following consecutive years of poor grain harvests. This document is VM123, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1, 2002.